Botanical and biological pesticides elicit a similar Induced Systemic Response in tomato (Solanum lycopersicum) secondary metabolism. (October 2016) - Pretali, Luca; Bernardo, Letizia; Butterfield, Timothy S.; Trevisan, Marco; Lucini, Luigi
Abstract: Natural pesticides have attracted substantial interest due to the increase in organic agriculture and enhanced attention to environmental pollution. Plant Growth Promoting Bacteria (PGPB) are applied for both disease control and growth enhancement; PGPBs are known to elicit Induced Systemic Response (ISR) in plants. However, less is known about the effect of botanical pesticides, such as the azadirachtin-containing neem extracts, on plant metabolism. This study aimed to investigate the effects of foliar application of the above-mentioned natural pesticides on the metabolic profiling of tomato. Leaf application of Bacillus subtilis fostered Induced Systemic Resistance (ISR) in treated plants via the Jasmonic acid pathway, and enhanced production of secondary metabolites such as flavonoids, phytoalexins and auxins. Changes in sterols and terpenes, as well as an increase in glucosinolates were also observed. Interestingly, azadirachtin-treated tomatoes also showed an increase in ISR and our results revealed that most of the enriched metabolites are shared with a B. subtilis treatment, suggesting conserved biochemical responses. These (un)expected findings indicate that plants are not insensitive to application of natural pesticide and while Azadirachtin is applied as a direct pesticide, it also stimulates a defense response in tomatoes very similar to B. subtilis induced ISR. Graphical abstract: Tomato metabolism was not insensitive to application of organic pesticide, and the botanical extract Azadirachtin elicited defense in a way very similar to a Bacillus subtilis formulation. Highlights: A Bacillus subtilis formulation fostered Induced Systemic Resistance in tomato leaves. Secondary metabolism was triggered, e.g. for flavonoids, phytoalexins and auxins. Azadirachtin metabolic response was largely shared with B. subtilis . Conserved biochemical responses were observed in both treatments.